Rapid quantification and PK-PD modeling of rocuronium bromide in beagles using portable mass spectrometer - Li, Xiaoxiao; Chang, Pan; Liu, Xing; Gong, Deying; Zhang, Wensheng (Frontiers in Veterinary Science, 2025)
Monitoring rocuronium bromide (Rocur) concentrations is crucial for assessing muscle relaxation in clinical anesthesia. However, no suitable instruments are currently available. This study explores the application of a portable mass spectrometer (MS) for the rapid detection of Rocur concentrations in whole blood from beagles, aiming to support the development of individualized pharmacokinetic-pharmacodynamic (PK-PD) models. Four beagles (1–1.5 years old, 8–12 kg) received a single intravenous dose of Rocur (3 ED₅₀, 0.748 mg/kg). Neuromuscular monitoring was conducted using the train of four (TOF) ratio. Blood samples (0.1 mL) were collected at predetermined intervals and during recovery, with TOF ratios recorded at corresponding time points. Rocur concentrations in whole blood (Cb-Rocur) were quantified using both the Cell portable MS and high-performance liquid chromatography with mass spectrometry (HPLC-MS) for consistency assessment. Additionally, a PK-PD model was developed based on Cb-Rocur measurements obtained from the Cell portable MS. A strong linear relationship was observed for Cell portable MS measurements within the range of 50–10,000 ng/mL (y = 1108.32 * x + 14873.99, R2 = 0.993), with a limit of quantification (LOQ) of 50 ng/mL and a limit of detection (LOD) of 10 ng/mL. A strong linear correlation was found between the two techniques (y = 1.07 * x + 30.08, p < 0.0001, R2 = 0.8948), with a relative standard deviation <15% for all concentrations. The Cmax values were 4.52 ± 1.16 μg/mL (Cell portable MS) and 4.89 ± 0.52 μg/mL (HPLC-MS), respectively. As Cb-Rocur decreased, the TOF ratio gradually recovered, with an IC50 of 0.25 ± 0.05 μg/mL. This study successfully applied the Cell portable MS for rapid quantitative Rocur analysis in whole blood, demonstrating high consistency with HPLC-MS. The findings also revealed the good correlation between the PK-PD properties of Rocur and TOF effects.